Analisis Penerapan Profil Pelajar Pancasila Berbasis Budaya Literasi di SDN 1 Brantaksekarjati - Siti Milkhatun Nadiroh; Imaniar Purbasari; Diana Ermawati (Journal on Education, 2023)
The application of literacy in elementary schools is very important for the continuity of the learning process and in order to shape student character. Low awareness of literacy is a problem in the application and development of student character. The purpose of this study was to find out how to implement character values based on the profiles of Pancasila students through the literacy culture at SDN 1 Brantaksekarjati. The method used is narrative-qualitative. The research was conducted at SDN 1 Brantaksekarjati in November 2022 with research subjects of class IV students, taking into account the criteria of the students' habits in the learning process and the homeroom teacher using data collection techniques in the form of observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and data retrieval. The validity of the data in the study was tested using a credibility test with method triangulation and source triangulation. The results showed that students had fulfilled 4 of the 6 indicators in applying the Pancasila student profile through literacy activities. Although the implementation of literacy activities in schools appears to be going well, individual student literacy awareness remains relatively low.